Distance function between structure of variants in consensus determining process in supply chain management systems - Sobieska-Karpińska, Jadwiga; Hernes, Marcin (Funkcja obliczania odległości pomiędzy strukturami wariantów w procesie wyznaczania consensusu w systemach wspomagających zarządzanie łańcuchem dostaw, 2013)
Consensus methods allow to resolve the knowledge conflicts, among other things, in supply chain management systems. The purpose of the article is to elaborate the distance function between the variants generated by the system SCM. This is one of the stages of the consensus determining process. The first part of the article presents a characteristic of knowledge conflicts, consensus methods and a definition of the structure of the variant. Next, the formal definition of distance function was elaborated. This definition is necessary in order to elaborate the algorithms of consensus determining.
Ekonometria = Econometrics, 2013, Nr 3 (41), s. 131-140
Keywords: supply chain management systems; knowledge conflicts; consensus methods; distance functions; systemy zarządzania łańcuchem dostaw; konflikty wiedzy; metody consensusu; funkcje odległości